2023
DOI: 10.3390/f14101951
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Vegetation Change and Its Climatic and Anthropogenic Driven Pattern in the Qilian Mountains

Yanmin Teng,
Chao Wang,
Xiaoqing Wei
et al.

Abstract: The Qilian Mountains (QLM) are an essential ecological security barrier in northwest China. Identifying the driven pattern of vegetation change is crucial for ecological protection and restoration in the QLM. Based on high-resolution vegetation coverage (VC) data in the QLM from 1990 to 2018, linear trend analysis was employed to examine the spatiotemporal dynamics of VC in the QLM, while correlation analysis was utilized to establish relationships between VC change and environmental factors. Multiple correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…At the macro-scale, this Special Issue discusses three aspects of forest ecosystem characteristics and management, i.e., characteristic identification [5][6][7][8], mechanism analysis [9][10][11], and optimization management [12].…”
Section: Mechanism Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…At the macro-scale, this Special Issue discusses three aspects of forest ecosystem characteristics and management, i.e., characteristic identification [5][6][7][8], mechanism analysis [9][10][11], and optimization management [12].…”
Section: Mechanism Analysismentioning
confidence: 99%
“…The authors suggested that ecological restoration projects enhanced the main ecological function of individual regions, and conducted a detailed analysis of the impacts of the "Grain for Green" project. Wen et al (2023) [6] proposed a three-step approach to explore the multi-aspect dynamics of land change, including the differences among land-use categories, spatial characteristics of urban expansion, and forest fragmentation, and explored characteristics of land-use change in a low-income mountainous city (Enshi City, China). The findings confirmed that recent planning measures were effective in restoring the natural environment, and that the identified key areas can support sustainable forest management during urban growth.…”
Section: Mechanism Analysismentioning
confidence: 99%
See 1 more Smart Citation